Voice from the Margin in Khagendra Sangraula’s Junkiriko Sangeet [The Music of the Firefly] - Rai, Man Kumar (JODEM: Journal of Language and Literature, 2022)
The women particularly from Dalit community are doubly under-shadowed in Khagendra Sangraula’s novel Junkiriko Sangeet [The Music of the Firefly]. The novel shows how women from Dalit community are tortured by their male partners and people from the so-called high caste people. The objective of this article is to study discrimination of Dalit women based on their caste, economic status and gender as women. The novel deals with the issue of Dalit, particularly Dalit women who have been physically and mentally exploited by upper caste people. This study shows how high caste people give stereotype identity to low caste people in order to impose their power over them. Sangraula depicts the harsh reality of Simring village where Dalit woman is fed stool and drunken men’s urine accusing her doing black magic. The Dalit women have no unity and some level of conscious to raise voice against such inhuman act. Therefore, their voice remains unheard. To analyze the issue explored above, this article takes theoretical ideas from Subaltern Studies, particularly from Gayatri Chakravarti Spivak, Gramsci and Foucault. The scholars of Subaltern Studies believe that subaltern group of people lack their own true representor which is the cause of remaining their issue at the bottom of social hierarchy. Some scholars believe that subaltern studies groups are like new historians who have to create discourse in order to re-write history of history less subaltern group. This paper also rewrites the ignored history of history less Dalit and Dalit women in Nepal.